The Development of Learning Tools in Project-Based Learning Oriented Creative Thinking - Nursamsu Nursamsu; Rachmatsyah Rachmatsyah (Postgraduate, University of Mataram, 2021)
Learning tools are a set of learning equipment arranged to support the learning process. The project-based learning model is considered as one of the excellent learning models in developing various basic skills within students, such as decision-making skills, creative thinking skills, and problem-solving skills. The design of research used a type validation study, which aims to prove learning theories. The results of the lesson plan validation test as the development of biology learning tools include a very feasible category with a score of 86.75%. The result of students’ worksheet validation is in a very good category with a value of 89.0%. The validation of teaching materials was categorized very well, with a value of 88.2%, and the validation of the evaluation sheet is in the very good category with a value of 88.53%. Furthermore, the practicality test to four teachers got responses about 78.13%, which indicates that the assessment is in good criteria. It can be concluded that the learning kits are feasible to be implemented in the learning activity process.